Customer Focus in Pharmaceutical Marketing in India - Das, P. K. (Indian Journal of Marketing, 2010)
Adrian Payne (2002) asked two questions to six hundred senior and middle level executives from large to medium sized service companies. The first question was, "Does your Chief Executive claim your organization is market driven, market-oriented or customer-focused?" Approximately 75% of managers claimed that these or similar terms were used by their Chief Executives. When he asked the second question "What percentage of the top 200 service organizations in this country are really customer-focused?". The average response was between 10 to 20 per cent. It seemed that there was an enormous gap in the services’ sector between those organizations that claimed to be customer-focused and those which actually were.